Conciencia tributaria en estudiantes del v semestre de la carrera profesional de contabilidad del Instituto Superior Tecnológico Joaquín Reátegui Medina, Nauta –2022 - Fernandez Perez, Edgar Josias (2023)
The present research work entitled "Tax Awareness in Students of the V Semester of the Professional Accounting Career of the Joaquín Reátegui Medina Higher Technological Institute, Nauta - 2022", was developed with the objective of determining the level of Tax Awareness that the Students of the V Semester of the Professional Accounting Career of the Joaquín Reátegui Medina Higher Technological Institute of the city of Nauta, for which it was estimated to carry out the descriptive type of research, being the non-experimental design, and 41 students who were considered as study population. They voluntarily decided to participate in this research work, to whom the survey technique was assigned and the questionnaire as an instrument; having carried out the analysis of the results, it was determined that 74.20% have a medium level and 25.80% have a low level in terms of compliance with tax obligations and in terms of motivation to pay tax obligations, 67 .6% have a medium level and 32.4 have a low level, it was concluded that students have a medium level of tax awareness.